2011
DOI: 10.1097/brs.0b013e318205e3af
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Evaluation of a Novel Fenestrated Pedicle Screw Augmented With Bone Cement in Osteoporotic Spines

Abstract: Significant increases in pullout strength can be accomplished by injecting a limited quantity of bone cement through a fenestrated screw while minimizing the risks associated with higher volume. The majority of implants were removed without damaging the vertebra as the bone cement sheared off at the fenestrations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
58
2
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(67 citation statements)
references
References 22 publications
3
58
2
4
Order By: Relevance
“…1,7,14,17,21,24 The main difference among these FPSs is the number of side perforations. Regardless of the different number of perforations, the pullout strength of PMMA-augmented FPSs is greater than that of nonaugmented conventional screws 3,5,9,10,12,26 or cannulated screws 8,16,18 in the osteoporotic condition. In the present study, compared with the nonaugmented CPS group, FPS-A1.0, 1.5, and 2.0 achieved 137%, 207%, and 265% increased pullout strengths, respectively, and FPS-B1.0, 1.5, and 2.0 achieved 166%, 232%, and 269% increased pullout strengths, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…1,7,14,17,21,24 The main difference among these FPSs is the number of side perforations. Regardless of the different number of perforations, the pullout strength of PMMA-augmented FPSs is greater than that of nonaugmented conventional screws 3,5,9,10,12,26 or cannulated screws 8,16,18 in the osteoporotic condition. In the present study, compared with the nonaugmented CPS group, FPS-A1.0, 1.5, and 2.0 achieved 137%, 207%, and 265% increased pullout strengths, respectively, and FPS-B1.0, 1.5, and 2.0 achieved 166%, 232%, and 269% increased pullout strengths, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, FPSs with different designs have been studied in vitro [3][4][5][8][9][10]12,16,18,26 and in vivo. 1,7,14,17,21,24 The main difference among these FPSs is the number of side perforations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They also found that the failure rate of CPS can be reduced by reducing the number of the radial hole. Although the effect of parameters of the radial holes (diameter and position of radial holes) on failure rate of CPS have been proof experimentally and numerically by several researchers [4][5][6][7][8][9][10], the optimum position and diameter of radial holes still becoming one of the gap in this research field. Thus, the aim of this paper is to propose the design optimization of cannulated pedicle screw which focuses more on optimization of diameter and position of radial holes.…”
Section: Introductionmentioning
confidence: 99%